Comparing the Frequency and Barriers in Performing Mammography in Different Occupations in 2018 - Heivari, Kh. (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Screening for early detection of breast cancer has been proven useful with mammography as one of the most important one of these methods. Mammography screening in women is essential, but it is evidently not being done in a timely manner among many Iranian women. Given the limited studies done in relation to the health of employed women, the present study was done to compare the frequency of doing mammography screening and the barriers in different occupations. Methods: This descriptive-analytic study was done on 895 married women aged 40–60, who were selected using convenience sampling, working in health care, educational, administrative, service, and homemaker groups in Shush, Andimeshk, and Dezful, in selected centers. Data were collected using a researcher-made questionnaire of screening barriers, demographic information, and a checklist for data screening and analyzed in SPSS 21. Results: Most of the samples in all five groups had not performed mammography screening. Doing regular mammography was 14.5% for health care group, 8.4% for educational group, 7.3% for administrative group, 5% for homemaker group, and 4.5% for services group. The results of ANOVA test of the individual barriers scores showed that the barriers related to lack of awareness, economic/social barriers, and the barriers related to providers in the groups were statistically significant. Conclusion: The screening rate is low in employed women that can be due to various individual and structural barriers, so doing educational interventions at different levels are suggested to remove barriers and increase the level of their performance.